MARKETING OF INLAND FISH IN ANAND, GUJARAT - PANIGRAHY, SHAKTI RANJAN; MISHRA, SNEHAL; VAHONIYA, DILIP; KUMAR, SANJIV (Journal of the Inland Fisheries Society of India, 2021)
Anand is number one district of Gujrat in inland fishery production through ponds and tanks. In the particular district, rohu, catla, nagri, surimai and bighead are abundantly found and large number of middlemen come between producer and consumer that increases marketing cost and margin. In this juncture, marketing efficiency, price spread and farmers' share in consumer rupee were decided for study purpose. This study was undertaken in the month of April-May, 2015 in eight taluka of Anand district purposively through a pre structured schedule. Rohu was observed as efficiently marketed than other categories of fish. It also generated larger share in consumer rupee for the producer and it was the only category of fish that was marketed in all the identified channels of the region. Marketing efficiency was better for larger fish and poor for the smaller ones. In all the channel the farmers' share in consumer rupee for bighead fish was constant but for Nagri it was very poor. Itinerant traders were earning maximum profit in marketing of Bighead fish. As the overall study area was completely unorganised, cooperatives and SHG may improve the marketing efficiency of the particular region.Key Words: Marketing efficiency, price spread, farmers' share in consumer rupee, inland fish